2019
DOI: 10.1634/theoncologist.2019-0067
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib in Patients with Antiangiogenic-Naïve and Chemotherapy-Refractory Advanced Colorectal Cancer: Results from a Phase IIb Trial

Abstract: Background Regorafenib is a multikinase inhibitor with antiangiogenic effects that improves overall survival (OS) in metastatic colorectal cancer (mCRC) after failure of standard therapies. We investigated the efficacy and safety of regorafenib in antiangiogenic therapy‐naïve chemotherapy‐refractory advanced colorectal cancer. Patients and Methods This single‐center, single‐arm, phase IIb study (NCT02465502) enrolled adults with mCRC whose disease had progressed on, or who were intolerant to, standard therapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…As favorable clinical factors associated with OS in regorafenib therapy, we revealed that 1M-RDI ≥ 50% (HR 0.16, 95% CI 0.05–0.50, p = 0.001) and HFSR during regorafenib therapy (HR 0.06, 95% CI 0.01–0.28, p = 0.0004) were independently associated with OS. Previous studies [23,24,25] reported that patients with metastatic colorectal cancer who were treated with regorafenib—and who experienced HFSR—showed better OS than patients without HFSR. The correlation of HRSR and survival has also been reported in the patients who enrolled the RESORCE trial [26].…”
Section: Discussionmentioning
confidence: 99%
“…As favorable clinical factors associated with OS in regorafenib therapy, we revealed that 1M-RDI ≥ 50% (HR 0.16, 95% CI 0.05–0.50, p = 0.001) and HFSR during regorafenib therapy (HR 0.06, 95% CI 0.01–0.28, p = 0.0004) were independently associated with OS. Previous studies [23,24,25] reported that patients with metastatic colorectal cancer who were treated with regorafenib—and who experienced HFSR—showed better OS than patients without HFSR. The correlation of HRSR and survival has also been reported in the patients who enrolled the RESORCE trial [26].…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic side effect of regorafenib is hand-foot skin reaction. Various studies have reported on the relationship between the grade of hand–foot skin reaction caused by regorafenib and survival time [ 17 , 18 ] and the prognostic factors that affect survival time [ 18 ]. In particular, a Phase IIb study on patients with metastatic CRC treated with regorafenib reported that patients with ≥ grade 2 hand–foot skin reaction have longer survival times than patients with grade 0–1 hand–foot skin reaction [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in CORRECT, all patients received prior bevacizumab and 52% received prior anti-EGFR therapy versus 41% and 35%, respectively, in CONCUR, which may contribute to the greater OS benefit in CONCUR [3,4,27]. More recently, a single-arm, phase 2b study evaluating regorafenib in antiangiogenic-naïve patients with chemotherapy-refractory, advanced CRC reported a median PFS and OS of 3.5 and 7.4 months, respectively [28], consistent with CONCUR, but comparing favorably with CORRECT. In the randomized, phase 2 REVERCE study, previously treated patients with mCRC receiving regorafenib followed by cetuximab (plus irinotecan) had better survival outcomes versus cetuximab followed by regorafenib, supporting the rationale for introducing regorafenib earlier in the treatment sequence [29].…”
Section: Mcrcmentioning
confidence: 99%